Pelaksanaan Perjanjian Kredit Antara PT Bank Rakyat Indonesia dengan Petani Sawah di Kecamatan Sukolilo Kabupaten Pati - Ma'ruf, Umar; Rifqi Andresta Putra (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
A credit agreement is an agreement made between a debtor and a creditor that creates a debt relationship, where the debtor has an obligation to repay the loan given by the creditor, based on the terms and conditions agreed upon by the parties. This study aims to determine the implementation of the credit agreement between PT Bank Rakyat Indonesia and rice farmers in Sukolilo District, Pati Regency and to determine the obstacles and solutions in the implementation of the credit agreement. This study uses a juridical-empirical research approach method with a sociological legal approach, the specifications in the study are descriptive analysis, with data collection techniques through library studies and interviews, which are used qualitatively. The results of the study indicate that the implementation of the credit agreement between Bank Rakyat Indonesia (BRI) and rice farmers in Sukolilo District, Pati Regency, is in accordance with Article 1338 of the Civil Code. The legal relationship formed creates the rights and obligations of both parties, in order to improve economic welfare. In obtaining credit at Bank BRI, obstacles are faced by rice farmers, for example, spelling errors, crop failures and credit risks. The solution provided by the bank is to correct the error to the relevant party, namely the Population and Civil Registration Service. Problems, with the existence of agricultural insurance and credit guarantees. Defaults that arise in the future can be resolved properly by both parties.